Answer:
[tex]g(w) = 210+ 10w[/tex]
Step-by-step explanation:
Given
[tex]f(w) = 250 + 10w[/tex]
[tex]Withdrawal = \$40[/tex]
Required
Determine g(w)
First, we'll write an expression for g(w)
From the question, we understand that she withdrew $40 from her account balance in w weeks.
This implies that:
[tex]g(w) = f(w) - 40[/tex]
Where f(w) is the account balance in w weeks and $40 is the withdrawn amount
Substitute 250 + 10w for f(w)
[tex]g(w) = 250 + 10w - 40[/tex]
Collect Like Terms
[tex]g(w) = 250 - 40+ 10w[/tex]
[tex]g(w) = 210+ 10w[/tex]
Recall that:
[tex]g(w) = f(w) - 40[/tex]
This means that function f(w) when shifter by 40 units downward, gives g(w)